2020
DOI: 10.1002/jcb.29826
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of immunomodulatory, proliferative, and antioxidant activities of crocin and crocetin on mesenchymal stem cells

Abstract: Saffron (Crocus sativus L) is a well‐known spice with active pharmacologic components including crocin, crocetin, safranal, and picrocrocin. Similar to crocin/crocetin, mesenchymal stem cells (MSCs) have been shown to display immunomodulatory and antioxidant properties, which could be beneficial in treatment of various diseases. In the current study, we have evaluated the effects of crocin and crocetin on the functions of MSCs. We used the 3‐(4,5‐dimethyl‐2‐thiazolyl)‐2,5‐diphenyl‐2H‐tetrazolium bromide assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The major components of saffron have been studied in animal and cellular models and have been shown to have positive effects on the level and activity of enzymes involved in cellular antioxidant activity, such as CAT and SOD. Meanwhile, the levels of recognized markers of OS, such as MDA (an indicator of the peroxidation of lipids), were shown to be decreased after treatment with saffron constituents (reviewed in Lopresti & Drummond, 2014 ; Yousefi et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The major components of saffron have been studied in animal and cellular models and have been shown to have positive effects on the level and activity of enzymes involved in cellular antioxidant activity, such as CAT and SOD. Meanwhile, the levels of recognized markers of OS, such as MDA (an indicator of the peroxidation of lipids), were shown to be decreased after treatment with saffron constituents (reviewed in Lopresti & Drummond, 2014 ; Yousefi et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Saffron tea has been reputed to be a potential complementary treatment for psoriasis in medical nutrition therapy [13]. Many pharmacological studies have shown that this plant and its phytochemicals have emerged as nutraceutical elements, endowed with beneficial effects on health showing antibacterial [14], antioxidant, cytotoxic [15,16], antifungal [17], immunomodulatory [18,19], anti-mutagenic [20], aphrodisiac [21], antitussives [22,23], and antiplatelet effects [24]. Traditional and modern biomedical reports have also proved saffron to cure coronary artery diseases [25], respiratory diseases [26], menstrual disorders [27,28], and neurodegenerative disorders [29].…”
Section: Introductionmentioning
confidence: 99%
“…The medium was replaced to remove non-adherent cells every 2 days. When the monolayer cells reached about 90% confluence, were detached from the culture flask by applying 25% Trypsin-EDTA Gibco for more tests (Yousefi et al 2020).…”
Section: Isolation Of At-mscs From Ms Patients and Healthy Individualmentioning
confidence: 99%